Hospital-based herpes zoster diagnoses in Denmark: rate, patient characteristics, and all-cause mortality - Schmidt, Sigrun A. J. (BMC Infect Dis, 2016)
BACKGROUND: Herpes zoster (HZ) may result in severe complications requiring hospital treatment, particularly in patients with comorbidity. Nevertheless, data on HZ from nationwide population-based hospital registries are sparse. METHODS: We conducted a cohort study describing first-time hospital-based (inpatient, outpatient, and emergency room) HZ diagnoses in the Danish National Patient Registry, 1994–2012. We computed the diagnosis rate; prevalence of demographic characteristics, comorbidities, and complications; length of hospital stay; and standardized mortality ratios (SMRs) using the Danish population as reference. We classified comorbidity using the Charlson Comorbidity Index (CCI) scoring system and categorized patients in groups of no (score 0), moderate (score 1), severe (score 2), and very severe comorbidity (score ≥3). In addition, we computed the prevalence of certain conditions associated with immune dysregulation (stem cell or bone marrow transplantation, solid organ transplantation, HIV infection, primary immunodeficiency, any cancer, and autoimmune diseases). RESULTS: The diagnosis rate increased almost exponentially from 6 to 91.9 per 100,000 person-years between age 50 and ≥90 years. The age-standardized rate was stable throughout the study period. The median length of hospital stay was 4 days (interquartile range: 1–8 days) for inpatients with HZ as the main reason for admission. According to the CCI, 44.3 % of patients had no comorbidity, 17.3 % moderate comorbidity, 17.4 % severe comorbidity, and 21.0 % very severe comorbidity. Comorbidities involving immune dysregulation, such as malignant (21 %) and autoimmune diseases (17 %), were particularly prevalent. Thirty percent had neurological, ophthalmic, or other complications. HZ was associated with increased all-cause mortality overall (SMR 1.8, 95 % CI: 1.7–1.8), but not in analyses restricted to patients without comorbidity (SMR 1.0, 95 % CI: 0.9–1.0). CONCLUSIONS: This study provides estimates of the epidemiology of hospital-based (severe) HZ. The diagnosis rate increased substantially with age. Complications and comorbidities were prevalent, likely resulting in increased mortality. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-016-1369-6) contains supplementary material, which is available to authorized users.